Managing Neurophobia: How Can We Meet the Current and Future Needs of Our Students? - Tarolli, Christopher G.; Józefowicz, Ralph F. (Seminars in Neurology, 2018)
Neurophobia was defined more than two decades ago as a “fear of neural sciences and clinical neurology” among medical students. Despite recognition of the ailment and research into underlying causes, medical students and neurological educators continue to struggle with neurophobia today. At our institution, we have been successful at mitigating neurophobia. Here, we define the underlying drivers of neurophobia, based on the relevant literature. We also describe our strategies for battling neurophobia in the preclinical and clinical years by (1) establishing a continuum of neurological education; (2) incorporating active and observed learning throughout neurological education; and (3) enhancing socialization into neurology. Finally, we consider the future of neurological education, describe strategies for educators to mitigate neurophobia, and propose a call to action to further understand neurophobia. Neurophobia is not inevitable; effective curricula and dedicated faculty can engage students and ensure students better understand and enjoy their neurological education.
Keywords: neurological education; neurophobia; neuroscience; medical students